2022
DOI: 10.1088/1748-0221/17/03/p03019
|View full text |Cite
|
Sign up to set email alerts
|

Developing a protocol for 90Y bremsstrahlung imaging after Transarterial Radioembolization

Abstract: Yttrium-90 (90Y) is an almost pure beta emitter used in Transarterial Radioembolization (TARE). Post-TARE 90Y bremsstrahlung imaging is employed for quantification of the delivered dose. 90Y bremsstrahlung imaging is the most challenging issue in nuclear medicine because of the low photon yield, the continuous and non-pronounced peak of the bremsstrahlung spectrum. GATE Monte Carlo code was employed to find the most proper imaging protocol for 90Y bremsstrahlung imaging. Images were acquired using Medium-Energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These ranges are consistent with other investigations related energy window optimization with medium energy collimator [6,8,12,13]. Namely, due to the Y-90 Bremsstrahlung energy spectrum has large numbers of low-energy photons, it is concluded that 50-100 keV energy window is the most proper energy window when using the medium energy collimator [23]. Spectral components of 225-300 keV and 300-400 keV in 90Y bremsstrahlung spectrum correspond the region of backscatter, collimator scatter and septal penetration [13].…”
Section: Optimal Imaging Conditions For Planar Imagessupporting
confidence: 90%
See 3 more Smart Citations
“…These ranges are consistent with other investigations related energy window optimization with medium energy collimator [6,8,12,13]. Namely, due to the Y-90 Bremsstrahlung energy spectrum has large numbers of low-energy photons, it is concluded that 50-100 keV energy window is the most proper energy window when using the medium energy collimator [23]. Spectral components of 225-300 keV and 300-400 keV in 90Y bremsstrahlung spectrum correspond the region of backscatter, collimator scatter and septal penetration [13].…”
Section: Optimal Imaging Conditions For Planar Imagessupporting
confidence: 90%
“…It should also be said that a medium energy collimator was used for Y-90 bremsstrahlung imaging in this study and results may vary if a high energy collimator is used. Since the low count of bremsstrahlung photons is the main problem in Y-90 imaging, in case of using high energy collimator, wider ranges of energy width can be resulted in images with an appropriate combination of sensitivity and quality [8,23].…”
Section: Optimal Imaging Conditions For Planar Imagesmentioning
confidence: 99%
See 2 more Smart Citations